2017
DOI: 10.1155/2017/6827384
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence of Cervical Cancer in Jordan, 2000–2013

Abstract: Objectives. To determine the incidence of cervical cancer in Jordan and assess its trend in over a 14-year period (2000–2013). Methods. This descriptive study was based on secondary analysis of cervical cancer data that are registered in the Jordan Cancer Registry (JCR). Results. A total of 591 women were diagnosed with cervical cancer in Jordan during the period 2000–2013. The age at diagnosis ranged between 15 and 97 years, with a median of 50 years. The average age standardized rate (ASR) was 2.0/100,000 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This goes with the trend of many countries as reported by the Globocan study, 30 Saudi Arabia, 27 and Jordan. 31 Cervical cancer remains the fourth most common female cancer contributing to 7.5% of all female cancer deaths in 2012, 19 but it forms l < 5% of female cancer deaths in Iraq. 32…”
Section: Discussionmentioning
confidence: 99%
“…This goes with the trend of many countries as reported by the Globocan study, 30 Saudi Arabia, 27 and Jordan. 31 Cervical cancer remains the fourth most common female cancer contributing to 7.5% of all female cancer deaths in 2012, 19 but it forms l < 5% of female cancer deaths in Iraq. 32…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that the average age standardized rate (ASR) was 2.0/100,000 women. Over the 14-year period, the ASR for cervical cancer has decreased by 28.6% from 2.1 per 100,000 women in 2000 to 1.5 per 100,000 women in 2013 [ 21 ]. The reason for that may be related to the low prevalence of risk factors of cervical cancer in Jordan including multiple sex partners.…”
Section: Discussionmentioning
confidence: 99%
“…Such data have been used by many investigators who studied the disease trends and published their research in reputable journals. Recently, in 2017, 2 papers were published on the trends of cancer using the surveillance data [ 12 , 13 ].…”
Section: The Jordan Field Epidemiology Training Programmentioning
confidence: 99%